2018
DOI: 10.1634/theoncologist.2017-0364
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumor Heterogeneity Adds Uncertainty to the World Health Organization 2010 Classification: Real-World Data from the Spanish Tumor Registry (R-GETNE)

Abstract: Gastroenteropancreatic neuroendocrine neoplasms are tumors of widely variable clinical behavior, roughly stratified by the World Health Organization (WHO) 2010 classification into three subgroups based on proliferation index. Real-world data from 2,813 patients of the Spanish Registry RGETNE demonstrated substantial clinical heterogeneity within grade (G) 2 and G3 neuroendocrine neoplasms. Tumor morphology and further subdivision of grading substantially improves prognostic stratification of these patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 24 publications
5
50
0
Order By: Relevance
“…Regarding the tumor characteristics, the grading defined by Ki-67 proliferation index is considered an established strong prognostic factor in numerous series (21,22,23). Our paper demonstrates how tumor grading significantly correlates with overall survival in malignant insulinomas.…”
Section: Discussionmentioning
confidence: 67%
“…Regarding the tumor characteristics, the grading defined by Ki-67 proliferation index is considered an established strong prognostic factor in numerous series (21,22,23). Our paper demonstrates how tumor grading significantly correlates with overall survival in malignant insulinomas.…”
Section: Discussionmentioning
confidence: 67%
“…Research so far has identified stage, site of origin [4] and differentiation [5 6], as well as proliferative indices (Ki-67, mitotic count) as important prognostic factors and multiple scores have been published, trying to predict survival in metastatic disease or recurrence after curative surgery [5][6][7][8][9][10][11]. In general, well-differentiated tumors progress slowly and surveillance may be the best approach in some cases, whereas poorly differentiated neoplasms require urgent aggressive chemotherapy and are associated with markedly shorter survivals [12]. Tumors of small bowel origin tend to have a better prognosis [13] compared to NENs originating in the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, grade 2 NETs form a very heterogeneous group and survival in this group can be very different between a "low" grade 2 with a Ki67 close to 2% or a "high" grade 2 with a Ki67 close to 20%. In our study, a cut off of 5% turned out to be more relevant than a cut off of 2% for Ki67, which has already been suggested (3,6,23). The WHO classification of NET should therefore probably be revised.…”
Section: Discussionmentioning
confidence: 57%